ANALYSIS OF THE LIMITATIONS OF TERRITORIAL RIGHTS FOR MILITARY ACTIVITIES IN THE EEZ OF A COASTAL STATE IN THE CASE OF THE US FONOPS ON LAKSHADWEEP ISLAND - Tri Widiastuti; Mubaraq, Othman Ballan, Arga Chon Feriandref, Eka Ermala, Duwi Aryadi (JOURNAL OF LAW AND NATION, 2023)
The rights, freedoms, and jurisdiction of states, whether coastal states have EEZs or not, are all regulated in UNCLOS. Maritime user States do not have additional rights beyond the scope of UNCLOS; therefore, coastal states can restrict relevant activities of other States in their EEZ. Regarding the legal status of the EEZ, this greatly influences the military activities of other countries in the EEZ of a coastal country. Therefore, military activities of other countries carried out in the EEZ of a coastal country are expected to be used under UN peace principles. Given inconsistent state practices, the international community must reconsider the relationship between the principles of peace and a state's military activities in the EEZ of other states to codify state practices and create universally acceptable norms. In this case, the steps that need to be taken in the form of legislative patterns can be used to design a country's military activities in another country's EEZ. Other countries do not need to provide prior notification before entering the EEZ of a coastal country. However, suppose a State adheres to the idea that all of its EEZ represents international waters and that the coastal state enjoys only economic jurisdiction. In that case, it does not require prior notification, as national security interests do not impact the economic jurisdiction of the coastal state. Other countries can then enjoy complete freedom of navigation and overflight in the coastal country's EEZ. As strategic partners, India and the US must take the first initiative to improve strategic policies in developing international maritime law. This awareness requires the formation of more relevant laws in legal politics that influence the practical behavior of countries toward the need to achieve common interests, such as inviting all countries to discuss, form, and renew international customary law in UNCLOS 1982, which is relevant for continuity in maintaining maritime policy order. Internationally, consistently, and in a balanced manner is practiced by countries, each of which fulfills the security interests of forces at sea.